Embedded star formation in S4G galaxy dust lanes - Elmegreen D.; Elmegreen B.; Erroz-Ferrer S.; Knapen J.; Teich Y.; Popinchalk M.; Athanassoula E.; Bosma A.; Comerón S.; Efremov Y.; Gadotti D.; De Paz A.; et al. (Institute of Physics Publishing, 2022)
Star-forming regions that are visible at 3.6 μm and Hα but not in the u, g, r, i, z bands of the Sloan Digital Sky Survey are measured in five nearby spiral galaxies to find extinctions averaging ∼3.8 mag and stellar masses averaging ∼5 × 10 M . These regions are apparently young star complexes embedded in dark filamentary shock fronts connected with spiral arms. The associated cloud masses are ∼10 M . The conditions required to make such complexes are explored, including gravitational instabilities in spiral-shocked gas and compression of incident clouds. We find that instabilities are too slow for a complete collapse of the observed spiral filaments, but they could lead to star formation in the denser parts. Compression of incident clouds can produce a faster collapse but has difficulty explaining the semi-regular spacing of some regions along the arms. If gravitational instabilities are involved, then the condensations have the local Jeans mass. Also in this case, the near-simultaneous appearance of equally spaced complexes suggests that the dust lanes, and perhaps the arms too, are relatively young. © 2014. The American Astronomical Society. All rights reserved.